Survival Responses of Two Termite Genera to Environmental Stressors as Bioindicators of Climate Change - Kuswanto, Eko; Pratama, Anisa Oktina Sari; Moh. Dwi Kurniawan Hasan; Aksel Fadly Masamanda; Zikri Al Rosyid; Ferry Andreansyah; Nico Okta Arniansyah (Jurnal Biodjati, 2025)
Termites are sensitive to environmental fluctuations and hold potential as bioindicators of climate change. This study evaluated the survivability of Nasutitermes and Macrotermes under controlled variations in temperature, relative humidity (RH), and CO₂ concentration. Laboratory experiments were conducted using eleven temperature levels (0–50°C), seven RH levels (40–100%), and four CO₂ concentrations (500–2000 ppm). Each treatment was replicated three times with 50 worker termites per replicate. Survivability, measured as percent survival after one hour of exposure, was analyzed by one-way ANOVA followed by Tukey’s HSD test (p < 0.05). The results indicated that both genera exhibited sharp declines in survival under temperature extremes and elevated CO₂. Optimal survivability for Nasutitermes and Macrotermes occurred at moderate temperatures (25–35°C), relative humidity (60–80%), and ambient CO₂ levels (500 ppm), while extreme conditions significantly increased mortality. The study highlights species-specific tolerance thresholds and confirms that environmental stressors directly affect termite physiology and behavior. These results confirm termites’ potential as reliable bioindicators, providing a practical tool for monitoring ecosystem responses to climate stress and informing strategies for sustainable ecosystem management.